2014
DOI: 10.1007/s40279-014-0281-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Proposal of a Field-Based Physical Fitness-Test Battery in Preschool Children: The PREFIT Battery

Abstract: The present systematic review has identified a need for further research on the validity of fitness tests in preschool children, as well as on their relationship with health. Due to this limited information, the PREFIT battery hereby proposed is based on the output of the current systematic review in preschool children, together with existing evidence in older children and adolescents. While we wait for more evidence to be accumulated in preschool children, the PREFIT battery hereby proposed is a useful tool f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
208
1
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(237 citation statements)
references
References 71 publications
(154 reference statements)
7
208
1
21
Order By: Relevance
“…Notwithstanding that such a fitness battery was used in adolescents, other studies such as AVENA, FitnessGram, or EUROFIT, have used similar fitness batteries to evaluate physical fitness levels in children [11,12,16,17]. Another similar battery is that proposed by the PREFIT study used in Spanish schoolchildren [18].…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding that such a fitness battery was used in adolescents, other studies such as AVENA, FitnessGram, or EUROFIT, have used similar fitness batteries to evaluate physical fitness levels in children [11,12,16,17]. Another similar battery is that proposed by the PREFIT study used in Spanish schoolchildren [18].…”
Section: Introductionmentioning
confidence: 99%
“…4x10m 4x4m; Ortega et al 2015), however this test was chosen in order to limit complexity as only 1 change in direction is required.…”
Section: Bot-2 Shuttle-runmentioning
confidence: 99%
“…As young children tend to accumulate their daily physical activity in short, intense intermittent bouts (Baquet et al 2007), short-term muscle power may be extremely relevant to their habitual activity patterns. In a recent systematic review by Ortega and colleagues (Ortega et al 2015), the authors identified the need for validation studies as no studies to date have examined the criterion-related validity of field-based MF assessments in preschoolers. The standing long jump (standing broad jump) and…”
mentioning
confidence: 99%
“…Además, se incluyen dos variantes: batería ALPHA-Fitness de alta prioridad (incluye todos los test excepto la medida de pliegues cutáneos) y batería ALPHA-Fitness extendida (incluye todos los test y además del test de velocidad y agilidad de 4 x 10 m). Una revisión sistemática recientemente publicada ha sugerido la batería PREFIT (evaluando el fitness en preescolares), la cual, tras revisar los estudios existentes sobre fiabilidad, validez y relación con la salud de los diferentes test de condición física usados en niños de edad preescolar o actualmente en Educación Infantil (3-5 años), propone los mismos test que en la batería ALPHA-Fitness extendida más el test de equilibrio a una pierna (63). Del mismo modo, un estudio reciente ha creado una adaptación del test original de ida y vuelta de 20 m para ser usado en población preescolar, demostrando ser un test máximo y fiable (64).…”
Section: Condición Físicaunclassified
“…Observaron también que, para una capacidad aeróbica dada, este grupo tenía un mejor pronóstico futuro que el resto de obesos y similar a personas con normopeso metabólicamente sanas (193). Una revisión en profundidad de la literatura existente en esta temática (195) concluye que hasta la fecha, solo un estudio ha explorado si estas diferencias en capacidad aeróbica observadas en población adulta existen también en adolescentes (n = 108) (196). Los autores observaron una mayor capacidad aeróbica en adolescentes obesos metabólicamente sanos que en el resto de compañeros obesos (consumo máximo de oxígeno = 44,0 vs. 42,7 ml/kg/min, respectivamente), aunque estas diferencias no fueron significativas.…”
Section: Niños Con Sobrepeso/obesidad Pero En Forma (Fat But Fit)unclassified